PEDOT: PSS / CNTs thermoelectric composite film with high thermoelectric performance and preparation method thereof

By physically blending PEDOT:PSS with CNTs and surface treatment using ionic liquid methanol solution, the problems of complex treatment steps and use of toxic chemicals in the prior art are solved, and PEDOT:PSS/CNTs thermoelectric with high thermoelectric performance are achieved Composite film, with high conductivity, Seebeck coefficient and power factor, and is easy to operate.

CN119421631AActive Publication Date: 2025-02-11TIANJIN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411391668.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-02-11
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

In the prior art, methods for improving the thermoelectric properties of PEDOT:PSS often involve complex processing steps and may use toxic and harmful chemicals, limiting their mass production and application.

Method used

By physically blending PEDOT:PSS aqueous solution with carbon nanotubes (CNTs), a PEDOT:PSS/CNTs composite film is formed, and surface treatment is used with an ionic liquid methanol solution to adjust the oxidation level and phase separation structure, and the thermoelectric properties of the film are improved.

Benefits of technology

The PEDOT:PSS/CNTs thermoelectric composite film with high thermoelectric properties has a high conductivity and Seebeck coefficient, and has a high power factor. The ionic liquid used is a green solvent, which is simple and safe to operate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119421631A_ABST
    Figure CN119421631A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of thermoelectric material preparation, and particularly relates to a high-thermoelectric-performance PEDOT: PSS / CNTs thermoelectric composite film and a preparation method thereof. The preparation method comprises the following steps: uniformly mixing PEDOT: PSS and CNTs to obtain a mixed solution; coating a substrate with the mixed solution to obtain a PEDOT: PSS / CNTs composite film; and carrying out surface treatment on the PEDOT: PSS / CNTs composite film by using an ionic liquid methanol solution to obtain the PEDOT: PSS / CNTs thermoelectric composite film. The PEDOT: PSS / CNTs thermoelectric thin film with high thermoelectric performance is obtained simply through two steps of operation of a physical blending method and ionic liquid surface treatment, the preparation method is simple, the thermoelectric performance is remarkably improved, and the obtained PEDOT: PSS / CNTs thermoelectric thin film has relatively high conductivity and Seebeck coefficient and also has a relatively high power factor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermoelectric material preparation, and in particular to a high-thermoelectric performance PEDOT:PSS / CNTs thermoelectric composite film and a preparation method thereof. Background Art

[0002] Thermoelectric technology uses efficient thermoelectric materials to convert collected heat into electrical energy, providing huge green energy for human society. Inorganic thermoelectric materials have the advantage of excellent thermoelectric performance, but have disadvantages such as fragile texture and high content of toxic heavy metals; while organic thermoelectric materials have the advantages of low cost, support for processing, and solution production, but have the disadvantage of poor thermoelectric performance. For example, PEDOT:PSS material has outstanding advantages in conductivity and film-forming properties, and has attracted much attention in the field of organic electronics research and application.

[0003] At present, there are various methods to improve the thermoelectric properties of PEDOT systems, such as doping, side chain engineering, and multi-component composite strategies. In addition to the above methods, the performance of PEDOT can also be improved by simple post-treatment methods. In recent years, the post-treatment methods of PEDOT include acid-base treatment, inorganic salt solution treatment, and polar solvent treatment. The thermoelectric properties of PEDOT can be improved by changing its phase separation structure and conformation. However, these post-treatment schemes usually involve complex processing steps, some of which may even require toxic and hazardous chemicals, which may pose an obstacle to the large-scale production and application of PEDOT. Therefore, it is very necessary to develop a new method to enhance the thermoelectric properties of PEDOT:PSS (poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid)) films. Summary of the invention

[0004] The purpose of the present invention is to provide a PEDOT:PSS / CNTs thermoelectric composite film with high thermoelectric performance and a preparation method thereof, wherein the obtained film has both high electrical conductivity and Seebeck coefficient to solve the problems existing in the above-mentioned prior art.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention is to provide a method for preparing a PEDOT:PSS / CNTs thermoelectric composite film with high thermoelectric performance, the steps comprising:

[0007] The PEDOT:PSS aqueous solution and carbon nanotubes (CNTs) are uniformly mixed to obtain a mixed solution;

[0008] Applying the mixed solution to a substrate to obtain a PEDOT:PSS / CNTs composite film;

[0009] The PEDOT:PSS / CNTs thermoelectric composite film is obtained by surface treating the PEDOT:PSS / CNTs composite film with an ionic liquid methanol solution.

[0010] Furthermore, the brand of the PEDOT:PSS aqueous solution is Clevios PH1000.

[0011] Furthermore, the volume concentration of CNTs in the mixed solution is 10-50%, preferably 40-50%.

[0012] Furthermore, the substrate is a glass sheet, a silicon sheet or a PET substrate.

[0013] Furthermore, the coating amount is 0.02 mL / cm 2 .

[0014] Furthermore, the volume concentration of the ionic liquid in the ionic liquid methanol solution is 10 to 50%, preferably 20 to 50%.

[0015] Furthermore, the ionic liquid is 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIM-BF4), 1-allyl-3-methylimidazolium tetrafluoroborate (AMIM BF4) or 1-allyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AMIM NTF2).

[0016] Furthermore, the dosage of the ionic liquid methanol solution is 0.02 mL / cm 2 .

[0017] Furthermore, the surface treatment step includes:

[0018] The ionic liquid methanol solution is dripped onto the surface of the PEDOT:PSS / CNTs composite film, and then spin-coated after standing.

[0019] Preferably, the standing time is 10 min.

[0020] Preferably, the spin coating parameters are: the first step speed of the coating machine is 1000 rpm, the time is 30 seconds, and the acceleration is 100 rpm s -1 The second step of the glue machine has a speed of 5000 rpm, a time of 30 seconds, and an acceleration of 1000 rpm s -1 .

[0021] Furthermore, the method further includes standing at 60° C. for 10 minutes after the surface treatment, cooling, rinsing with ethanol at least once, and then drying at 60° C. for 30 minutes.

[0022] The second technical solution of the present invention is to provide a PEDOT:PSS / CNTs thermoelectric composite film with high thermoelectric performance prepared by the above preparation method.

[0023] The PEDOT:PSS / CNTs thermoelectric composite film of the present invention is prepared by compounding PEDOT:PSS and CNTs by a physical blending method, and then using an ionic liquid methanol solution for surface treatment. It has both high electrical conductivity and Seebeck coefficient. There are two factors that contribute to the high electrical conductivity of the PEDOT:PSS / CNTs thermoelectric composite film. One is the carrier concentration, and the other is the conductive structure. The first step is to add CNTs to the PEDOT:PSS aqueous solution by a physical blending method. As the amount of CNTs mixed increases, the conductivity of the composite film increases accordingly. CNTs have a conjugated polyene structure, and the π electrons show extremely strong delocalization. It and the π electrons on the main chain of the thiophene ring are conjugated through π-π to construct a new conjugated system, forming a carrier transmission channel, which is beneficial to improving the transmission of carriers, thereby improving the conductivity of the composite material. When the CNTs content is 50%, the conductivity of the sample drops to 90.1S cm -1 This is mainly due to the uneven dispersion of CNTs, which blocks the connection between PEDOT molecular chains, resulting in a downward trend in the conductivity of the composite material. The second step of ionic liquid (IL) treatment can adjust the oxidation level. The ionic liquid EMIM-BF4 is used as a secondary dopant. The interaction between PEDOT and PSS is weakened by ionic liquid treatment, inducing phase separation between PEDOT and PSS, and part of Tos is removed in the subsequent washing process. The conductive network structure is further optimized, which increases the conductivity.

[0024] The third technical solution of the present invention is to provide a method for improving the conductivity and power factor of PEDOT:PSS / CNTs film while maintaining the stability of the Seebeck coefficient, the steps comprising:

[0025] The PEDOT:PSS aqueous solution and CNTs are uniformly mixed to obtain a mixed solution;

[0026] Applying the mixed solution to a substrate to obtain a PEDOT:PSS / CNTs composite film;

[0027] The PEDOT:PSS / CNTs thermoelectric composite film is obtained by surface treating the PEDOT:PSS / CNTs composite film with an ionic liquid methanol solution.

[0028] The present invention discloses the following technical effects:

[0029] The present invention provides a PEDOT:PSS / CNTs thermoelectric composite film with high thermoelectric performance. The PEDOT:PSS / CNTs composite film is prepared by a physical blending method in the first step. Compared with the PEDOT:PSS material, the Seebeck coefficient and the electrical conductivity of the composite film are increased. After the ionic liquid treatment in the second step, the electrical conductivity can be significantly improved while maintaining the relative stability of the Seebeck coefficient. The PEDOT:PSS / CNTs thermoelectric film obtained by the present invention has both high electrical conductivity and Seebeck coefficient, and also has a high power factor.

[0030] The present invention compounds organic thermoelectric materials with inorganic micro-nano materials to prepare organic thermoelectric materials with better comprehensive performance. This improvement strategy can also be introduced into other material systems to enhance the performance of other material systems.

[0031] The invention simply obtains a high thermoelectric performance PEDOT:PSS / CNTs thermoelectric film by two steps of physical blending and ionic liquid surface treatment, and the preparation method is simple and the thermoelectric performance is significantly improved. The EMIM-BF4 ionic liquid used as a green solvent has the advantages of low volatility, stability, and easy recycling. Compared with the strong acid, strong base or other toxic reagents used in the traditional method, it has the advantages of simple and safe operation. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 is the conductivity of the PEDOT:PSS film in Comparative Example 1 and the PEDOT:PSS / CNTs composite films in Examples 1 to 5;

[0034] Figure 2 is the Seebeck coefficient of the PEDOT:PSS film in Comparative Example 1 and the PEDOT:PSS / CNTs composite films in Examples 1 to 5;

[0035] Figure 3 is the power factor of the PEDOT:PSS film in Comparative Example 1 and the PEDOT:PSS / CNTs composite films in Examples 1 to 5;

[0036] Figure 4The electrical conductivity of the PEDOT:PSS / CNTs composite film and the high thermoelectric performance PEDOT:PSS / CNTs thermoelectric composite film in Example 1, and the high thermoelectric performance PEDOT:PSS / CNTs thermoelectric composite film in Examples 6 to 7;

[0037] Figure 5 is the Seebeck coefficient of the PEDOT:PSS / CNTs composite film and the high thermoelectric performance PEDOT:PSS / CNTs thermoelectric composite film in Example 1, and the high thermoelectric performance PEDOT:PSS / CNTs thermoelectric composite film in Examples 6 to 7;

[0038] Figure 6 It is the power factor of the PEDOT:PSS / CNTs composite film and the high thermoelectric performance PEDOT:PSS / CNTs thermoelectric composite film in Example 1, and the high thermoelectric performance PEDOT:PSS / CNTs thermoelectric composite film in Examples 6 to 7. DETAILED DESCRIPTION

[0039] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0040] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0041] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0042] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0043] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0044] The raw materials and reagents used in the specific embodiments of the present invention are all commercially available products.

[0045] The PEDOT:PSS aqueous solution used in the specific embodiment of the present invention is provided by Hoexter Company and has the brand name Clevios PH1000, wherein the weight ratio of PEDOT to PSS is 1:2.5 and the concentration is 1.3 wt %.

[0046] The substrate used in the specific implementation scheme of the present invention is a glass sheet. It should be noted that the role of the substrate in the present invention is to serve as a carrier for the film. When other substrates (silicon wafers or PET substrates) specified in the present invention are selected, the same technical effects can be achieved. Therefore, based on their roles in the present invention, they can be equally replaced.

[0047] The ionic liquid used in the specific embodiment of the present invention is 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIM-BF4). It should be noted that based on the role of the ionic liquid in the present invention, the three ionic liquids defined in the present invention are 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIM-BF4), 1-allyl-3-methylimidazolium tetrafluoroborate (AMIM BF4) and 1-allyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AMIM NTF2), which can be equally replaced.

[0048] Example 1

[0049] The preparation steps of high thermoelectric performance PEDOT:PSS / CNTs thermoelectric composite film are as follows:

[0050] S1. After mixing the PEDOT:PSS aqueous solution (Clevios PH1000) and CNTs, the mixture was stirred continuously for 12 hours using a magnetic bar to prepare a uniform mixed solution with a CNTs volume concentration of 40%;

[0051] S2. Select a glass sheet as a substrate, and ultrasonically clean the glass sheet (1 cm×1 cm) with deionized water, acetone, and isopropanol for 15 minutes, respectively. Then, use a nitrogen gun to blow dry the surface of the glass sheet, lay it flat in a culture dish, and treat the glass sheet with oxygen plasma at a power of 80 W and an oxygen flow rate of 0.3 to 0.4 mbar for 10 minutes. Store the clean substrate in the culture dish for later use;

[0052] S3, taking out the glass substrate obtained in step S2 and placing it in a mask plate, placing the mask plate in the inner cavity of the inorganic evaporation, and preparing a chromium-gold electrode; the evaporation rate of the chromium (Cr) electrode is The thickness of the evaporated film is 4nm; the evaporation rate of the evaporated gold (Au) electrode is The thickness of the evaporated film is 30 nm. After the evaporation is completed, take out the sample, remove the glass slide with tweezers, and place it in a clean culture dish for later use.

[0053] S4, treating the glass sheet with chromium-gold electrodes with oxygen plasma at a power of 100 W and an oxygen flow rate of 0.3-0.4 mbar for 10 minutes, placing it at the rotation center of a glue spreader after cleaning, using a pipette to draw 20 μL of the mixed solution obtained in step S1 to evenly cover the surface of the glass sheet, and then drying it in a vacuum oven at 50°C to obtain a PEDOT:PSS / CNTs composite film with a CNTs volume concentration of 40%;

[0054] S5. Prepare a 20% volume concentration EMIM BF4 methanol solution: dissolve EMIM BF4 in methanol at room temperature, and ultrasonically oscillate the prepared solution for 24 hours to form a uniform solution;

[0055] S6. Pipette 20 μL EMIM BF4 methanol solution and spin coat it on the PEDOT / CNTs composite film. Turn on the coating machine to perform two-step film spinning. The first step of the coating machine has a rotation speed of 1000 rpm, a time of 30 seconds, and an acceleration of 100 rpm s -1 The second step of the glue machine has a speed of 5000 rpm, a time of 30 seconds, and an acceleration of 1000 rpm s -1 After the spin coating is completed, the sample is placed on a hot stage at 60°C for 10 minutes and cooled naturally. The cooled film is rinsed three times with anhydrous ethanol to remove the residual EMIM-BF4 on the surface. The film is then placed on a hot stage at 60°C to dry for 30 minutes. After drying, a film treated with EMIM BF4 methanol solution with a volume concentration of 20% is obtained, which is recorded as a high thermoelectric performance PEDOT:PSS / CNTs thermoelectric composite film.

[0056] Example 2

[0057] Compared with Example 1, the only difference is that the volume concentration of CNTs in the mixed solution in step S1 is 50%.

[0058] Example 3

[0059] Compared with Example 1, the only difference is that the volume concentration of CNTs in the mixed solution in step S1 is 10%.

[0060] Example 4

[0061] Compared with Example 1, the only difference is that the volume concentration of CNTs in the mixed solution in step S1 is 20%.

[0062] Example 5

[0063] Compared with Example 1, the only difference is that the volume concentration of CNTs in the mixed solution in step S1 is 30%.

[0064] Example 6

[0065] Compared with Example 1, the only difference is that in step S5, a methanol solution of EMIM BF4 with a volume concentration of 10% is prepared.

[0066] Example 7

[0067] Compared with Example 1, the only difference is that in step S5, a methanol solution of EMIM BF4 with a volume concentration of 50% is prepared.

[0068] Comparative Example 1

[0069] The preparation steps of PEDOT:PSS film are as follows:

[0070] S1. Select a glass sheet as a substrate, ultrasonically clean the glass sheet (1 cm×1 cm) with deionized water, acetone, and isopropanol for 15 minutes, then use a nitrogen gun to blow dry the surface of the glass sheet, lay it flat in a culture dish, and treat the glass sheet with oxygen plasma at a power of 80 W and an oxygen flow rate of 0.3-0.4 mbar for 10 minutes, and store the clean substrate in the culture dish for later use;

[0071] S2, taking out the glass substrate obtained in step S1 and placing it in a mask plate, placing the mask plate in the inner cavity of the inorganic evaporation, and preparing a chromium-gold electrode; the evaporation rate of the chromium (Cr) electrode is The thickness of the evaporated film is 4nm; the evaporation rate of the evaporated gold (Au) electrode is The thickness of the evaporated film is 30 nm. After the evaporation is completed, take out the sample, remove the glass slide with tweezers, and place it in a clean culture dish for later use.

[0072] S3. Treat the glass sheet with chromium-gold electrode with oxygen plasma at a power of 100 W and an oxygen flow rate of 0.3-0.4 mbar for 10 minutes. After cleaning, place it at the rotation center of the glue spreader. Use a pipette to absorb 20 μL PEDOT:PSS to evenly cover the surface of the glass sheet. Turn on the glue spreader for two-step film spinning. The first step of the glue spreader has a rotation speed of 1000 rpm, a time of 30 seconds, and an acceleration of 100 rpm s -1The second step of the glue machine has a speed of 5000 rpm, a time of 30 seconds, and an acceleration of 1000 rpm s -1 , and then dried in a vacuum oven at 50°C to obtain a PEDOT:PSS film.

[0073] Test example

[0074] The conductivity, Seebeck coefficient and power factor of the PEDOT:PSS film in Comparative Example 1, the PEDOT:PSS / CNTs composite films in Examples 1 to 7 and the PEDOT:PSS / CNTs thermoelectric composite films in Examples 1 to 7 were tested. The results are as follows: Figures 1 to 6 shown.

[0075] Figure 1 is the conductivity of the PEDOT:PSS film in Comparative Example 1 and the PEDOT:PSS / CNTs composite films in Examples 1 to 5; Figure 2 is the Seebeck coefficient of the PEDOT:PSS film in Comparative Example 1 and the PEDOT:PSS / CNTs composite films in Examples 1 to 5; Figure 3 It is the power factor of the PEDOT:PSS film in comparative example 1 and the PEDOT:PSS / CNTs composite film in examples 1 to 5. In the figure, the abscissa is the volume concentration of CNTs in the mixed solution when the composite film is prepared in the examples and comparative examples.

[0076] Depend on Figures 1 to 3 It can be seen that at room temperature, the conductivity of the PEDOT:PSS film in Comparative Example 1 (CNTs addition amount is 0) is 7.5S cm -1 , Seebeck coefficient is 17.7μV K -1 As the amount of CNTs added increases, the conductivity of the composite film increases. In Examples 3 to 5, the amount of CNTs added was 10%, 20%, and 30%, respectively, and the conductivity, Seebeck coefficient, and power factor were all improved. The conductivity was 22.3, 33.2, and 49.9 S cm, respectively. -1 ( Figure 1 ), and the Seebeck coefficients are 21.9μV K -1 , 28.8μV K -1 , 34.9μV K -1 ( Figure 2 ). When the volume concentration of CNTs is 10% (Example 3), the power factor is 1.08 μW m -1 K -2 , the CNTs content continued to increase to 30% (Example 5), the power factor gradually increased ( Figure 3). In general, the thermoelectric performance of the PEDOT:PSS / CNTs thermoelectric composite film with a CNTs volume concentration of 40% (Example 1) is the best, with an electrical conductivity of 177.5S cm -1 S cm -1 , the Seebeck coefficient is 40.2 μW m -1 K -2 , the corresponding power factor is 28.71μW m -1 K -2 .

[0077] Figure 4 The electrical conductivity of the PEDOT:PSS / CNTs composite film and the high thermoelectric performance PEDOT:PSS / CNTs thermoelectric composite film in Example 1, and the high thermoelectric performance PEDOT:PSS / CNTs thermoelectric composite film in Examples 6 to 7; Figure 5 is the Seebeck coefficient of the PEDOT:PSS / CNTs composite film and the high thermoelectric performance PEDOT:PSS / CNTs thermoelectric composite film in Example 1, and the high thermoelectric performance PEDOT:PSS / CNTs thermoelectric composite film in Examples 6 to 7, Figure 6 It is the power factor of the PEDOT:PSS / CNTs composite film and the high thermoelectric performance PEDOT:PSS / CNTs thermoelectric composite film in Example 1, and the high thermoelectric performance PEDOT:PSS / CNTs thermoelectric composite film in Examples 6 to 7. In the figure, the abscissa is the volume fraction of the EMIM BF4 methanol solution when preparing the composite film in the examples and comparative examples.

[0078] Depend on Figures 4 to 6 It can be seen that the conductivity of PEDOT:PSS / CNTs composite film at room temperature is 177.5S cm -1 After the surface treatment with EMIM BF4 methanol solution, the conductivity was improved. In Examples 6 and 7, when the PEDOT:PSS / CNTs composite film was treated with 10% and 50% EMIM BF4 methanol solution, the conductivity was increased to 282.9Scm -1 and 373.1S cm -1 ( Figure 4 ); The Seebeck coefficient of the high thermoelectric performance PEDOT:PSS / CNTs thermoelectric composite film in Examples 1 and 6 to 7 is 42μV K -1 ~46μV K -1 Small fluctuations between Figure 5 ); and the power factor of PEDOT:PSS / CNTs composite film (28.71μW m -1 K -2), after surface treatment with EMIM BF4 methanol solution, the power factor was significantly improved. Among them, the power factors of the high thermoelectric performance PEDOT:PSS / CNTs thermoelectric composite films of Example 6 and Example 7 were 51.86 μW m -1 K -2 and 74.65 μW m -1 K -2 ( Figure 6 ); The surface treatment effect of Example 1 with EMIM BF4 methanol solution having a volume concentration of 20% was the best, and the conductivity increased significantly to 465.2S cm -1 , the Seebeck coefficient does not change much and remains stable, and the power factor is 95.96μW m -1 K -2 , the power factor is more than three times higher than that of PEDOT:PSS / CNTs composite film.

[0079] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a high thermoelectric performance PEDOT:PSS / CNTs thermoelectric composite film, characterized in that the steps include: The PEDOT:PSS aqueous solution and CNTs are uniformly mixed to obtain a mixed solution; Applying the mixed solution to a substrate to obtain a PEDOT:PSS / CNTs composite film; The PEDOT:PSS / CNTs thermoelectric composite film is obtained by surface treating the PEDOT:PSS / CNTs composite film with an ionic liquid methanol solution.

2. The preparation method according to claim 1, characterized in that The volume concentration of CNTs in the mixed solution is 10-50%.

3. The preparation method according to claim 1, characterized in that: The substrate is a glass sheet, a silicon sheet or a PET substrate; the coating amount is 0.02 mL / cm 2 .

4. The preparation method according to claim 1, characterized in that: The volume concentration of the ionic liquid in the ionic liquid methanol solution is 10-50%; the ionic liquid is 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-allyl-3-methylimidazolium tetrafluoroborate or 1-allyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide; the dosage of the ionic liquid methanol solution is 0.02 mL / cm 2 .

5. The preparation method according to claim 1, characterized in that: The surface treatment step comprises: dripping the ionic liquid methanol solution onto the surface of the PEDOT:PSS / CNTs composite film, allowing it to stand and then spin coating it.

6. The preparation method according to claim 5, characterized in that: The standing time is 10 min; the spin coating parameters are: the first step speed of the coating machine is 1000 rpm, the time is 30 seconds, and the acceleration is 100 rpm s -1 The second step of the glue machine has a speed of 5000 rpm, a time of 30 seconds, and an acceleration of 1000 rpm s -1 .

7. The preparation method according to claim 1, characterized in that: The method also includes standing the surface at 60° C. for 10 minutes after the surface treatment, cooling, rinsing with ethanol at least once, and then drying at 60° C. for 30 minutes.

8. A PEDOT:PSS / CNTs thermoelectric composite film with high thermoelectric performance prepared by the preparation method according to any one of claims 1 to 7.

9. A method for improving the conductivity and power factor of PEDOT:PSS / CNTs film while maintaining the stability of the Seebeck coefficient, characterized in that the steps include: The PEDOT:PSS aqueous solution and CNTs are uniformly mixed to obtain a mixed solution; Applying the mixed solution to a substrate to obtain a PEDOT:PSS / CNTs composite film; The PEDOT:PSS / CNTs thermoelectric composite film is obtained by surface treating the PEDOT:PSS / CNTs composite film with an ionic liquid methanol solution.

Citation Information

Patent Citations

  • Preparation method of self-standing PEDOT: PSS / SWCNTs composite flexible film with high thermoelectric performance

    CN114497341A

  • PEDOT: PSS flexible thermoelectric thin film with high thermoelectric performance and high air stability and preparation method and application of PEDOT: PSS flexible thermoelectric thin film

    CN115360291A

  • High-performance PEDOT: PSS flexible thermoelectric film and preparation method thereof

    CN117062507A

  • Organic thermoelectric material including organic weak base and organic thermoelectric element thereof

    KR1020170075039A

  • Organic thermoelectric material including organic weak base and organic thermoelectric element thereof

    KR1020180053630A